Mao. 9 - Takahashi, Rumiko, 1957- (Shonen Sunday comics special., 2023)
"Exorcise your destiny. When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way! Natsuno is compelled by a mysterious force to collect one grotesque item after another. Will she find what she seeks at a performance by a mysterious yokai theater troupe? Then, Yurako recalls how the Goko clan exploited her powers for profit. Plus, Nanoka goes undercover to investigate a teenager accused of cursing her classmate..."--Back cover.